Orbital scale lake evolution in the Ejina Basin, central Gobi Desert, China revealed by K-feldspar luminescence dating of paleolake shoreline features. (20th July 2018) - Li, Guoqiang; Madsen, David B.; Jin, Ming; Stevens, Thomas; Tao, Shuxian; She, Linlin; Yang, Liping; Li, Fangliang; Wei, Haitao; Duan, Yanwu; Chen, Fahu
Abstract: The Ejina Basin in the central Gobi Desert contains the terminal lakes of the Heihe River. Paleoenvironmental changes in the basin are important since its deposits are a significant source of Northern Hemisphere dust. In this study we employed a K-feldspar pIRIR dating technique to date shoreline features ≥940 m at multiple locations in the Ejina Basin ∼45–50 m above the modern basin floor. Internal checks of luminescence characteristics were employed to test the reliability of the pIRIR dating. In combination with our previously reported stratigraphy and chronology of shorelines at ≤927 m in the Ejina Basin, these results imply that a paleolake was present in the basin prior to ∼350 ka. Other high stands in the basin occurred at ∼320-310 ka, 240-180 ka, 120-80 ka, and ∼5 ka, corresponding to MIS 9, MIS 7, MIS 5 and the mid Holocene (MIS 1), respectively, indicating a strong link with glacial-interglacial cycles. Extensions of the East Asian Summer Monsoon (EASM) during interglacial periods, possibly interacting with the Westerlies, apparently caused higher precipitation and lake formation. The impact of orbital eccentricity on the EASM/Westerlies appears to be responsible for the formation of major lake/desert cycles on the northeastern margin of the Tibetan Plateau.